2014
DOI: 10.17795/mejrh-23470
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphs Show Higher Postural Sway Than Other Somatotypes Subjects

Abstract: Background:The somatotype may influence the balance control ability. The quality of balance performance is an important factor to prevent injuries during sport activities. Objectives: The purpose of this study was to investigate the influence of somatotype on the static and dynamic balance indices as well as falling risk index. Patients and Methods: A total of 141 university student healthy young females were recruited. We measured anthropometric somatotypes (10 parameters, Heath-Carter's method) and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Our results revealed that in comparison to endomorphs and mesomorphs, postural sway is increased in the ectomorphic subjects during static balance test. Our findings were consistent with the Allard et al (2001) and Farenc et al (2003) studies, which reported that ectomorphs presented the worst balance control in comparison to the other somatotypes, at the same time other researchers showed higher postural sway for endomorphs (Samaei et al, 2014). The results of the present study may indicate that ectomorphs, with lower body weight and less muscle mass, have more difficulty to control balance than endomorphs and mesomorphs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that in comparison to endomorphs and mesomorphs, postural sway is increased in the ectomorphic subjects during static balance test. Our findings were consistent with the Allard et al (2001) and Farenc et al (2003) studies, which reported that ectomorphs presented the worst balance control in comparison to the other somatotypes, at the same time other researchers showed higher postural sway for endomorphs (Samaei et al, 2014). The results of the present study may indicate that ectomorphs, with lower body weight and less muscle mass, have more difficulty to control balance than endomorphs and mesomorphs.…”
Section: Discussionsupporting
confidence: 92%
“…For the research were recruited 120 voluntary subjects, sporty and physically active. Of these, 83 subjects were included in the study, 42 women and 41 men (24 ± 4.4 years,height 171.4 ± 8.5 cm,weight 71.3 ± 15.3 Kg), specifically only the subjects with a somatotype-component dominant as regards the others (Samaei, 2014). Moreover, the subjects with postural problems, injuries and balance difficulties were excluded from the study.…”
Section: Participantsmentioning
confidence: 99%
“…The achieved data highlighted that the mesomorphic subjects had a better balance performance, while the performance of endomorphs was poor. Muscle strength and structure are useful for joint stability and postural control; the might be the main reason for the better performance of mesomorphs in our study (previous studies have supported the same finding) [11,12,29]. Unlike some previous studies, the ectomorphs in our study had better postural control than endomorphs.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the somatotype in young basketball players is closer to ectomorphy (Gryko et al, 2018), while in professional basketball players it is closer to mesomorphy (Gryko et al, 2018;Ochoa Martínez, Hall López, Alarcón Meza, Arráyales Millán, & Sánchez León, 2014). In other populations, it has been seen that an increase in body fat negatively affects postural balance (Guzmán-Muñoz, Valdés-Badilla, Mendez-Rebolledo, Concha-Cisternas, & Castillo-Retamal, 2018;Morales-Vargas, Valdes-Badilla, & Guzmán-Muñoz, 2021), while those with a mesomorphic somatotype show better postural balance (Samaei, Bakhtiary, & Hajihasani, 2014).…”
Section: Introductionmentioning
confidence: 97%